Investigating Gap between Customers’ Taste and Market Variety and its Impact on the Customer Satisfaction: An Empirical Study in the Automotive Industry - Mousavi, Seyed Farhad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This study investigates and examines the gap between customer preferences and market variety in the Iranian automobile market and its impacts on customer satisfaction. A linear approximation is used for the utility function of customers of the Iranian carmaker (Iran Khodro Co). Also the SERVQUAL model for measuring customer satisfaction is used to determine, the gap between customer expectation and perceived quality. The moderator variable called “Role of car in the customer life” is introduced and its effect on the relationships between customer expectation, perceived quality and customer satisfaction is evaluated. The results show that considering the history of car sales over the past five years compared with the value predicted by the existing car market share, a significant gap between the current sales of IKCO and a product assortment ideally adapted to the customers is detected. The highest gap occurred between the level of expectation and the perceived quality of factors, respectively belonging to sale, car accessories, technical and physical aspects and the after-sale services. In this way, companies can elaborate better strategies and production plans and can increase their market share. As a contribution, this study provides a method for identifying customer behavior based on choices among options consisting of a set of qualitative and quantitative factors. So the method presented in this study can be used to empower automakers corporations to increase their competitive advantage and create the readiness to enter and compete in global market. This could prevent decline in automakers share and increase their profitability through achieving customer satisfaction. We live in a dynamic and changing environment. Changes in customer tastes and purchasing power; Changes in technical standards specifically regulations related to polluting potential of cars and tariff regulations; Changes in market structure toward openness to global market and increasing competition, could reduce the applicability of this research results. So these are open questions for future researches. Also as a topic for further research, the number of vehicles and factors types can be changed to evaluate the market share. Also, the effect of the moderator variable on customer satisfaction for other useable products and services may be investigated.Öz:Bu çalışma İran otomobil piyasasındaki müşteri tercihleri ve pazar çeşitliliği arasındaki boluğu ve bunun müşteri memnuniyeti üzerindeki etkisini araştırmakta ve incelemektedir. İranlı otomobil üreticisi (İran Khodro Co) müşterilerinin yarar fonksiyonu için doğrusal bir yaklaşım kullanılmıştır. Ayrıca müşteri beklenti ve algılanan kalite arasındaki boşluğu belirlemek ve müşteri memnuniyetini ölçmek için SERVQUAL modeli kullanılmıştır. "Müşteri hayatında arabanın rolü" adlı moderatör değişken olarak tanıtılarak müşterinin beklentisi, kalite algısı ve müşteri memnuniyeti üzerindeki etkisi değerlendirilmiştir. Sonuçlar, son beş yıl içerisindeki otomobil satışlarıyla mevcut araç pazar payı içerisindeki değeri karşılaştırıldığında, IKCO’nun mevcut satış ve ideal müşterilerine uyarlanmış bir ürün yelpazesi arasında anlamlı bir fark tespit edilmiştir. En büyük fark, satış, araba aksesuarları, teknik be fiziksel donanım ve satış sonrası hizmetlerin beklenti düzeyi ve kalite faktör algıları arasında meydana gelmiştir. Bu şekilde, şirketler daha iyi strateji ve üretim planlarını hazırlayarakmak pazar paylarını artırabileceklerdir. İleri bir araştırma konusu olarak, araç ve faktör türlerinin sayısı değiştirilerek pazar payı değerlendirilmesi önerilmektedir. Ayrıca, diğer kullanışlı ürün ve hizmetler için müşteri memnuniyeti moderatör değişkenin etkisi araştırılabilir.
Doctor of Philosophy in Industrial Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2015. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Customer Relations; Customer Preferences; Utility function; Customer behavior; Microeconomics; Expectation; Perceived Quality; Customer Satisfaction; Moderating; Conditional Correlation